2017
DOI: 10.1021/acsbiomaterials.7b00641
|View full text |Cite
|
Sign up to set email alerts
|

R- and Z-Axis Patterned Scaffolds Mimic Tracheal Circumferential Compliance and Longitudinal Extensibility

Abstract: There remains no routine treatment for congenital tracheal abnormalities affecting more than 1/3 of the length. Natural and artificial prostheses are plagued by mechanical failure and inconsistent outcomes. Mimicking native tissue mechanics in an engineered replacement may improve functional and patient outcomes. We synthesized tubular constructs comprising photo-cross-linked methyl acrylate-co-methyl methacrylate, p­(MA-co-MMA), with patterned r- and z-axes in order to achieve mechanical properties similar to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Ultimately, we demonstrated that biomimetic patterning not only produced longitudinal extensibility but also simultaneously enhanced radial recoil . We further investigated construct compliance, and the role of tubular geometry in allowing for radial deformation of a physiological profile …”
Section: Trachea Replacement Strategies and Mechanicsmentioning
confidence: 97%
See 4 more Smart Citations
“…Ultimately, we demonstrated that biomimetic patterning not only produced longitudinal extensibility but also simultaneously enhanced radial recoil . We further investigated construct compliance, and the role of tubular geometry in allowing for radial deformation of a physiological profile …”
Section: Trachea Replacement Strategies and Mechanicsmentioning
confidence: 97%
“…Hoffman et al measured the longitudinal composite elastic modulus of porcine trachea specimens containing bands of cartilage and annular ligament and reported a modulus of 1.10 ± 0.68 MPa, which was significantly different from the tensile elastic modulus for cartilage alone . We reported a tensile composite modulus for juvenile ovine trachea of 1.5 ± 0.37 MPa, and a toe region modulus of 0.10 ± 0.04 MPa . Behrend et al evaluated the breaking strength of composite ovine trachea samples under longitudinal tension and found a mean breaking force of 198 N .…”
Section: Whole Organ Mechanical Properties and Implications Of Implan...mentioning
confidence: 99%
See 3 more Smart Citations